The Actor as Author of the Text he Acts - Nogueira, Marta (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2020)
We aim to demonstrate how the acting technique and skills of an actor may influence the intentions of a text’s author, showing him new paths through the human and emotional factors. We also aim to demonstrate that what is usually considered a “text” may not always be a fixed entity produced by a single isolated individual. The analysis of the staging and film adaptation of Tennessee Williams’ A Streetcar Named Desire and the development of the character Stanley Kowalski by Marlon Brando, shows how he changed the written version of the play, shifting its core, interfering with the balance between the two main characters and helping to shape the cultural and historical attributes which rendered its particular place in art history. The text produced by the actor may, thus, assume an identical value to that of the dramatic script from which it developed, or even produce a higher impact.